2020
DOI: 10.1002/jsfa.10330
|View full text |Cite
|
Sign up to set email alerts
|

The influence of harvesting time and meteorological conditions on the occurrence of Fusarium species and mycotoxin contamination of spring cereals

Abstract: BACKGROUND The aim was to determine the influence of harvesting time and meteorological conditions on the occurrence of Fusarium spp. and mycotoxins in the grain of spring cereals. A field experiment was performed in 2016–2018 with spring oat (Avena sativa L.) and spring triticale (× Triticosecale Wittm.) plots. Grain samples of oat and triticale were analysed for Fusarium infection and co‐contamination with mycotoxins deoxynivalenol (DON), zearalenone (ZEA) and T‐2 toxin (T‐2). RESULTS Results from the three‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Meanwhile, more than 97.8%, 98.4% and 95.7% complete feeds for pig, poultry and ruminant, respectively, were also co-contaminated with these three mycotoxins. These results were similar to previous reports which showed that mycotoxin co-contamination is a widespread issue in the feed industry [ 21 , 35 38 ]. Since the present feed safety regulations do not consider the potential toxicity of co-contamination of mycotoxins, their combined toxicity on animal health and production may be underestimated, and the combined toxicity of these mycotoxins warrants further study so that it might be considered when new regulatory limits for mycotoxins are set in the future.…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, more than 97.8%, 98.4% and 95.7% complete feeds for pig, poultry and ruminant, respectively, were also co-contaminated with these three mycotoxins. These results were similar to previous reports which showed that mycotoxin co-contamination is a widespread issue in the feed industry [ 21 , 35 38 ]. Since the present feed safety regulations do not consider the potential toxicity of co-contamination of mycotoxins, their combined toxicity on animal health and production may be underestimated, and the combined toxicity of these mycotoxins warrants further study so that it might be considered when new regulatory limits for mycotoxins are set in the future.…”
Section: Discussionsupporting
confidence: 93%
“…In the 2012–2014 period with extreme weather events, only Romania and Poland reported natural contamination with deoxynivalenol in triticale, values being similar in the regions from northeastern Romania and southeastern Poland that have close historical agroclimatic conditions due to geographic position (present study) [ 64 , 90 ]. For the 2016–2018 period, Lithuania reported natural contamination with deoxynivalenol in triticale, especially during the harvest period with heavy precipitation, leading to increased mycotoxin levels [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cereals and animal feed in Central Europe (45–52° N, 8–20° E) showed very high maximum values of deoxynivalenol contamination, especially between 49–52° N and 9–20° E (Eastern Moravia and northern Bohemia in the Czech Republic, Germany and southwestern Poland), compared to cereals in southeastern Europe (41–46° N, 15–25° E) and Eastern Europe (41–46° N, 15–25° E) ( Figure S.4 ) [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 90 , 91 , 92 , 93 , 110 , 111 , 112 , 113 ]. The higher deoxynivalenol contamination in cereals in Central Europe (southern Germany, the Czech Republic, western Slovakia and southwestern Poland) is due to precipitation caused by the intersection of Atlantic air masses with the “Vb” cyclones and low historical agroclimatic characteristics that have been amplified by extreme weather events in 2012–2014 ( Figure S.4 ) [ 19 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations